2010
DOI: 10.1016/j.jacc.2010.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium Progression: An Important Clinical Measurement?

Abstract: Baseline coronary artery calcification (CAC) accurately identifies coronary atherosclerosis and might improve prediction of future cardiac events. Serial assessment of CAC scores has been proposed for monitoring atherosclerosis progression and for assessing the effectiveness of medical therapies aimed at reducing cardiac risk. However, whether knowledge of progression of CAC scores over time further improves risk prediction is unclear. Several trials relating medical therapies to CAC progression have been perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
227
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(238 citation statements)
references
References 80 publications
7
227
1
3
Order By: Relevance
“…In the literature, calcification scoring via CT is often uniquely described but can usually be found in terms of severity, typically ranging from none or mild to severe or >130 Hu for CT angiography [8][9][10][11][12][13][14][15][16][17][18]. Methods for interpreting the score, however, have not been standardized.…”
Section: Techniques To Assess Coronary Calciummentioning
confidence: 99%
“…In the literature, calcification scoring via CT is often uniquely described but can usually be found in terms of severity, typically ranging from none or mild to severe or >130 Hu for CT angiography [8][9][10][11][12][13][14][15][16][17][18]. Methods for interpreting the score, however, have not been standardized.…”
Section: Techniques To Assess Coronary Calciummentioning
confidence: 99%
“…The relationships presented also suggest the merit of considering certain risk factors themselves as surrogates for coronary plaque burden over time and avoiding the need for (repeat) computed tomography. 3,15,[21][22][23][24] Previous studies of CAC risk factors have focused largely on the incidence rather than the progression of CAC. The studies that do look at progression are scarce and often conflict.…”
Section: Discussionmentioning
confidence: 99%
“…It predicts future cardiovascular risk beyond the traditional Framingham risk score alone 29, 30, 31, 32. An elevated CACS may portend an increased risk of cardiovascular events in some patients 33. Specifically, the MESA study (Multi‐Ethnic Study of Atherosclerosis) with 6722 patients followed for an average of 3.8 years showed that those with CACS >300 have a nearly 10‐fold increased risk of coronary event across ethnic groups 34.…”
Section: Multimodality Imaging Techniquesmentioning
confidence: 99%
“…However, there are important limitations of CACS including that it generally only represents ≈20% of total plaque volume, it cannot be used to determine if there is flow‐limiting stenosis, and it does not provide information on plaque morphology or subtype because of its lower resolution and poor tissue contrast 62. CACS CT imaging is also unable to detect calcification accurately at a molecular level33 and does not discriminate between microcalcification and macrocalcification, potential markers of vulnerable and stable atherosclerotic plaques, respectively 63, 64…”
Section: Multimodality Imaging Techniquesmentioning
confidence: 99%